2018
DOI: 10.1007/s10554-018-1417-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronary sinus flow is reduced in methamphetamine abusers: a transthoracic echocardiographic study

Abstract: To compare the coronary sinus flow among healthy participants, methamphetamine abusers without chest pain and those with chest pain. One hundred and eight methamphetamine abusers: 53 ones without chest pain, 55 ones with chest pain, free of ascertained coronary artery disease, were enrolled in this study. A control group of 50 age-matched male healthy participants was studied for comparison. Standard 2D, flow and tissue Doppler echo with measurements of cardiac morphologic and functional indicators, coronary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…distal coronary microvessels and capillary networks. These findings provided direct evidence for our previous studies in which methamphetamine has been shown to decrease coronary sinus flow and myocardial function [13,14].…”
Section: Discussionsupporting
confidence: 85%
“…distal coronary microvessels and capillary networks. These findings provided direct evidence for our previous studies in which methamphetamine has been shown to decrease coronary sinus flow and myocardial function [13,14].…”
Section: Discussionsupporting
confidence: 85%
“…Like cocaine, methamphetamine also may reduce coronary sinus blood flow. 7 It has been reported that up to 70% of methamphetamine users have an abnormal ECG, with the most common finding being tachycardia. 8 Additional abnormalities on the ECG have been attributed to presence of hypertension, pulmonary artery hypertension, and cardiomyopathy, all of which have been associated with methamphetamine use.…”
Section: Choosing the Right Pathway With Patient-centric Algorithms F...mentioning
confidence: 99%
“…Furthermore, impulsivity was the strongest predictor of PHYSQOL which refers to the patients' physical pain, fatigue, sleep, mobility, daily life, dependence on medical treatment, and ability to work (65). Previous studies have found that patients with SUDs tend to report physical discomfort, such as pain (66,67) and poor quality of sleep (68,69), which may interfere with their treatment. Our findings may provide advice to clinicians that reducing impulsivity may improve their perception of PHYSQOL, thereby promoting treatment.…”
Section: Discussionmentioning
confidence: 99%